Pencegahan Etnosentrisme Melalui Penanaman Nilai Civic Culture di Sanggar Seni Bougenvile - Ega Nur Cahya; Jagad Aditya Dewantara; Sulistyarini Sulistyarini; Okiri Peter Ochieng; Fitria Arifiyanti (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to investigate the effectiveness of implementing ethno-cultural identity values in the Bougenville art studio to prevent ethnocentrism. The research demonstrates that art learning and interactions among studio members contribute to the broadening of individuals' social perspectives. A qualitative research approach was employed, utilizing a case study method. The research participants included the head and trainer of the Bougenville studio, as well as the students and community members associated with the studio. Data collection techniques consisted of observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and drawing conclusions. The findings reveal that the Bougenville studio has a strategic approach in preserving local identity, considering its location in Pontianak where multiple ethnic groups coexist. The studio incorporates regular training programs and curriculum advancements. Although the focus is primarily on regional culture, particularly Melayu culture, it does not lead to an ethnocentric attitude among the studio's students. The Bougenville studio successfully promotes and upholds ethno-cultural values without fostering ethnocentrism among its residents.